Obesity Hypoventilation Syndrome with Cardiogenic Pulmonary Edema: Clinical Challenges in Airway and Ventilation Management in Critical Care Settings - Putri Rizkiya; Fajar Perdhana (Indonesian Journal of Anesthesiology and Reanimation, 2026)
Introduction: Obesity hypoventilation syndrome (OHS) manifests as a triad of obesity, chronic daytime hypercapnia, and disrupted breathing during sleep. These patients frequently present with respiratory complications that complicate airway management and increase the risk of atelectasis during mechanical ventilation. Objective: To present a clinical case involving a patient with obesity hypoventilation syndrome. Case Report: A 36-year-old female with morbid obesity arrived at the emergency department exhibiting acute dyspnea. Initial examination revealed shallow respirations and a respiratory rate of 40/min. Her oxygen saturation was 82%, which improved to 88–90% with high-flow nasal cannula (HFNC) at 60 L/min and FiO₂ 80%. A pulmonary exam indicated dullness to percussion and bilateral basal rales. Cardiovascular findings suggested inadequate cardiac compensation. A chest radiograph showed cardiomegaly and pulmonary congestion suggestive of edema. Arterial blood gas (ABG) analysis revealed acute hypoxemic respiratory failure with pH 7.09, PaCO₂ 135 mmHg, and PaO₂ 145 mmHg. Due to declining oxygen saturation and consciousness, the patient was intubated. Intubation was complicated by difficult mask ventilation and positioning challenges. Post-intubation atelectasis resolved after 48 hours of recruitment maneuvers. Acute pulmonary edema due to cardiogenic shock was treated with a negative fluid balance and continuous inotropic support, which led to better oxygenation as the doses of inotropes were lowered. Discussion: Patients with OHS admitted in critical condition often face more than just dyspnea. Management must also address cardiometabolic dysfunctions and complex respiratory challenges that necessitate advanced airway strategies and ICU-level care. Conclusion: This case highlights the complexity and clinical considerations required in the management of obesity hypoventilation syndrome.